Calculation of wet areas from the geometric modelling of the shape of sections of the lagoon of Cotonou,Benin - Codo, Francois de Paule; SENOU, Lauris (My University, 2017)
The main causes of the hydrologic and hydraulic changements which are taking place in the lagoon of Cotonou, are the construction of the seaport and the construction of the dam of Cotonou. They are the principal responsible for the trapping of the discharged sediments in the lagoon of Cotonou by the nokoué lake. This paper presents the first step and the boundary condition for the characterization of the hydrosedimentary dynamics study of the estuary of Cotonou. It aims to take into account the tranversal sections of the lagoon of Cotonou, small channel of the Ouémé River. The technique used consists to measure on big sections with an equidistance of three meters by moving the boat used for bathymetry from the first bank of the river (point 0) to the second one, and so on .The graduated cord ballasted with 5kg of lead to stop the waterflow from moving the cord, is submerged for measuring the depth of the lagoon. The measurement had taken place during the dry season. Then we calculate the wet areas from the geometric modelling of the shape of sections of the lagoon. This calculation which takes in account the bathymetry of the lagoon, is useful for a better appreciation of the evaluation of the evolution of the geometry of the sections of the lagoon and the evoluation of the sedimentary dynamics of sediments in the river
Keywords: bathymetry; dam; estuary; hydro-sedimentary dynamics; modeling; trapping